Complementary and alternative medicine (CAM) in women with endometriosis. (July 2021) - Adamietz, Alexandra; Boosz, Alexander; Mueller, Andreas; Hornung, Daniela; Trunk, Katharina; Beckmann, Matthias W.; Dittrich, Ralf; Hack, Carolin C.
Highlights: Endometriosis is highly debilitating for women affected. CAM therapy methods might be good options in case conventional therapies fail. Not enough research in this field yet for recommendations. Endometriosis patients are very interested in CAM but have a lack of information. Abstract: Objective: This study aimed to provide an overview of the extent to which women with endometriosis are informed about, interested in, and make use of CAM, and to evaluate which of the methods are most often applied. Study Design: A retrospective, two-center cohort study was conducted using a validated questionnaire among women with laparoscopically confirmed endometriosis at two urban teaching hospitals, certified as endometriosis centres. Results: A total of 592 patients were included in the study and received the questionnaire; 114 (19.3 %) were included in the data analysis. Most of the women were not receiving hormone therapy at the time of the study (n = 60, 52.6 %). Most (n = 75, 65.8 %) were interested in CAM, but only a minority (n = 12, 10.5 %) had detailed knowledge about it. A total of 81 patients (71.1 %) had used at least one CAM method for disease management; the five most frequently used CAM methods were exercise (n = 55, 48.2 %), vitamins (n = 40, 35.1 %), yoga (n = 38, 33.3 %), homeopathy (n = 32, 28.1 %), and trace elements (n = 27, 23.7 %). Conclusions: In our study population, women with endometriosis are strongly interested in using CAM, but have only limited information about it. Nevertheless, a majority of the patients had used at least one CAM method to relieve symptoms associated with the disease and the most often used was exercise.